2020
DOI: 10.3390/ijms21020641
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Attenuates Mitochondrial Alterations and Oxidative Stress Leading to Cell Death Induced by Very Long-Chain Fatty Acids in a Mouse Oligodendrocyte Model

Abstract: In the case of neurodegenerative pathologies, the therapeutic arsenal available is often directed towards the consequences of the disease. The purpose of this study is, therefore, to evaluate the ability of docosahexaenoic acid (DHA), a molecule present in certain foods and considered to have health benefits, to inhibit the cytotoxic effects of very long-chain fatty acids (C24:0, C26:0), which can contribute to the development of some neurodegenerative diseases. The effect of DHA (50 µM) on very long-chain fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Dihydroethidine (DHE) is a fluorescent probe that measures ROS production (including superoxide anions (O 2 •− )) by flow cytometry [ 69 , 74 ]. Indeed, the non-fluorescent probe (DHE) is rapidly oxidized by ROS, once it enters the cell, and forms ethidium (HE) which binds to DNA and exhibits an orange/red fluorescence in response to a blue excitation (λEx Max = 488 nm; λEm Max = 575 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Dihydroethidine (DHE) is a fluorescent probe that measures ROS production (including superoxide anions (O 2 •− )) by flow cytometry [ 69 , 74 ]. Indeed, the non-fluorescent probe (DHE) is rapidly oxidized by ROS, once it enters the cell, and forms ethidium (HE) which binds to DNA and exhibits an orange/red fluorescence in response to a blue excitation (λEx Max = 488 nm; λEm Max = 575 nm).…”
Section: Methodsmentioning
confidence: 99%
“…This is because the majority of ROS is produced within the mitochondrial respiratory chain as byproducts of ATP generation [ 41 ], and the imbalance between ROS and antioxidants within the mitochondria might be one of the crucial pathways leading to its dysfunction, further triggering the oxidative stress cascade. A recent study reported that treating 158 N cells with C26:0 at concentrations of up to 20 µM for 24 and 48 h induced cell death due to mitochondrial dysfunction and oxidative stress [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of male with fish oil drastically increased DHA contents in mitochondrial membrane of skeletal muscles. 33 DHA supplementation of the medium affects the cellular membrane 34 and is incorporated into the mitochondrial membrane, as determined by an increase in cardiolipin. 35 In addition, DHA increased MMP and susceptibility of the mitochondria to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%